2011
DOI: 10.1016/j.bandc.2011.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Musicians and tone-language speakers share enhanced brainstem encoding but not perceptual benefits for musical pitch

Abstract: Behavioral and neurophysiological transfer effects from music experience to language processing are well-established but it is currently unclear whether or not linguistic expertise (e.g., speaking a tone language) benefits music-related processing and its perception. Here, we compare brainstem responses of English-speaking musicians/non-musicians and native speakers of Mandarin Chinese elicited by tuned and detuned musical chords, to determine if enhancements in subcortical processing translate to improvements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
169
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(192 citation statements)
references
References 81 publications
20
169
3
Order By: Relevance
“…However, that study found no advantage for tone language speakers in the imitation of monotone sequences like those used here. Likewise, analyses of imitation accuracy across tone and nontone language speakers here yielded no differences, nor did comparisons of groups for BAIS subscales and the perceptual discrimination task (note that evidence for a tone language advantage for simple pitch discrimination is mixed; Bidelman, Gandour, & Krishnan, 2011).…”
Section: Third Variablesmentioning
confidence: 66%
“…However, that study found no advantage for tone language speakers in the imitation of monotone sequences like those used here. Likewise, analyses of imitation accuracy across tone and nontone language speakers here yielded no differences, nor did comparisons of groups for BAIS subscales and the perceptual discrimination task (note that evidence for a tone language advantage for simple pitch discrimination is mixed; Bidelman, Gandour, & Krishnan, 2011).…”
Section: Third Variablesmentioning
confidence: 66%
“…22 Musicians excel at both of these skills. 2,12,13 By this account then, musicians' stronger MOC activity may provide more antimasking at the probe signal frequency, enhancing its contrast from the noise masker, and consequently providing sharper estimates of filtering in that cochlear channel. Alternatively, stronger top-down efferent control in musicians 24 may allow them to preemptively inhibit MOC gain reduction (which can alter neural tuning curves 22 ) and thus maintain a higher degree of frequency resolution compared to nonmusicians.…”
Section: Discussionmentioning
confidence: 98%
“…13 The masker was a 300 ms pure tone gated with 5 ms cos 2 ramps. Tonal maskers had normalized frequencies of 0.12, 0.25, 0.50, 0.62, 0.75, 0.87, 1.00, 1.05, 1.12, 1.25, and 1.50 relative to the probe's CF.…”
Section: Forward Masked Ptcsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of this benefit to psychoacoustic measures of auditory abilities at present is unclear. Frequency and pitch discrimination has received the greatest attention in psychoacoustic studies of the effect of musical training (e.g., Spiegel and Watson, 1984;Micheyl et al, 2006;Parbery-Clark et al, 2009;Bidelman et al, 2011;Deguchi et al, 2012). Compared to nonmusicians, results have shown superior performance by musicians with the effect of psychoacoustic training of nonmusicians also evident when measured.…”
Section: Introductionmentioning
confidence: 99%